A Feasibility Study for in vivo Dosimetry Procedure in Routine Clinical Practice. (5th June 2018) - Falco, Maria D.; Giancaterino, Stefano; De Nicola, Andrea; Adorante, Nico; De Lorenzo, Ramon Gimenez; Di Tommaso, Monica; Vinciguerra, Annamaria; Trignani, Marianna; Perrotti, Francesca; Allajbej, Albina; Fidanzio, Andrea; Greco, Francesca; et al.
Purpose: The aim of the in vivo dosimetry, during the fractionated radiation therapy, is the verification of the correct dose delivery to patient. Nowadays, in vivo dosimetry procedures for photon beams are based on the use of the electronic portal imaging device and dedicated software to elaborate electronic portal imaging device images. Methods: In total, 8474 in vivo dosimetry tests were carried out for 386 patients treated with 3-dimensional conformal radiotherapy, intensity-modulated radiotherapy, and volumetric modulated arc therapy techniques, using the SOFTDISO. SOFTDISO is a dedicated software that uses electronic portal imaging device images in order to (1) calculate the R index, that is, the ratio between daily reconstructed dose and the planned one at isocenter and (2) perform a γ-like analysis between the signals, S, of a reference electronic portal imaging device image and that obtained in a daily fraction. It supplies 2 indexes, the percentage γ% of points with γ < 1 and the mean γ value, γmean . In γ-like analysis, the pass criteria for the signals agreement ΔS% and distance to agreement Δd have been selected based on the clinical experience and technology used. The adopted tolerance levels for the 3 indexes were fixed in 0.95 ≤ R ≤ 1.05, γ% ≥ 90%, and γmean ≤ 0.5. Results: The results of R ratio, γ-like, and a visual inspection of these data reported on a monitor screen permitted to individuate 2 classes of errors (1) class 1 that included errors due to inadequate standard quality controls and (2) class 2, due to patient morphological changes. Depending on the technique and anatomical site, a maximum of 18% of tests had at least 1 index out of tolerance; once removed the causes of class-1 errors, almost all patients (except patients with 4 lung and 2 breast cancer treated with 3-dimensional conformal radiotherapy) presented mean indexes values (R ¯, γ ¯ %, andγ ¯ mean ) within tolerance at the end of treatment course. Class-2 errors were found in some patients. Conclusions: The in vivo dosimetry procedure with SOFTDISO resulted easily implementable, able to individuate errors with a limited workload.